Preparation process of enameled wire for new energy photovoltaic power
By using polyurethane paint prepared by modified polyurethane and boron nitride in photovoltaic power systems, the cross-linking network is formed using Si-O bonds, oxime urethane bonds and Diels-Alder reactions, which solves the aging and damage of enameled wires and improves resistance Fuel, thermal stability and self-healing performance extends service life and improves safety.
Patent Information
- Application Number
- CN202411459714.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the existing photovoltaic power system, the enameled wires are prone to aging and damaged in outdoor environments, affecting the operation and service life of the equipment, and lacking excellent anti-aging and self-repairing performance.
Polyurethane paint is prepared by polyurethane and modified boron nitride. The thermal reversible crosslinking network is formed through Si-O bond, oxime urethane bond and Diels-Alder addition reaction, combining phosphorus elements and anthracene groups to enhance the flame retardant of the enameled wire. , thermal stability, anti-aging and self-healing properties.
It significantly improves the flame retardant, thermal stability, anti-aging and self-repairing performance of the enameled wire for new energy photovoltaic power, extends the service life and improves safety.
Smart Images

Figure BDA0005091526220000111 
Figure BDA0005091526220000121 
Figure BDA0005091526220000122
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wires and cables, and in particular to a preparation process of an enameled wire for new energy photovoltaic power. Background Art
[0002] Photovoltaic power generation, as a renewable energy technology, uses solar photons to generate electricity. With the increasing demand for clean energy and concerns about carbon emissions, photovoltaic power generation technology has been widely used and promoted around the world. In order to effectively collect, transmit and utilize the electricity generated by photovoltaic panels, high-quality cables and enameled wires suitable for these systems are required.
[0003] The main function of the enameled wire used in the new energy photovoltaic power system is to transmit the electricity generated by the solar panels. The photovoltaic power system is usually installed in the outdoor environment. The enameled wire is exposed to the natural environment such as sunlight, wind, and rain for a long time. The paint film on the outer layer of the enameled wire is easy to age and break, which affects the normal operation and service life of the equipment. Therefore, it is necessary to propose a preparation process for enameled wire for new energy photovoltaic power. The enameled wire prepared by the preparation process has excellent anti-aging and self-repairing properties, which greatly improves the service life and safety of the enameled wire and has broad market prospects. Summary of the invention
[0004] The purpose of the present invention is to provide a preparation process of enameled wire for new energy photovoltaic power to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A preparation process for an enameled wire for photovoltaic power generation of new energy, the preparation process for the enameled wire for photovoltaic power generation of new energy comprises the following steps: reacting polyurethane and 1-(9-anthryl)methylamine to obtain modified polyurethane; reacting pre-modified boron nitride and N-(2-aminopropyl)maleimide to obtain modified boron nitride; preparing polyurethane paint by mixing the modified polyurethane and the modified boron nitride; impregnating copper wire with the polyurethane paint and drying to obtain the enameled wire for photovoltaic power generation of new energy;
[0007] The polyurethane is prepared by polymerization reaction of 1-chloromethyl-2,4-diisocyanobenzene, hydroxyl-terminated polymethyltrifluoropropylsiloxane and dimethylglyoxime;
[0008] The pre-modified boron nitride is prepared by polymerizing 4-propyleneoxy-2-hydroxybenzophenone and allyl phosphoric acid on pre-treated boron nitride;
[0009] The pretreated boron nitride is prepared by treating boron nitride with allyltriethoxysilane.
[0010] As an optimization, the preparation process of the new energy photovoltaic power enameled wire includes the following preparation steps:
[0011] (1) Polyurethane, 1-(9-anthryl)methylamine, triethylamine, and N,N-dimethylformamide are uniformly mixed in a mass ratio of 1:(0.4-0.6):(0.02-0.04):(10-12), stirred at 40-50° C. and 300-500 r / min for 2-3 h, and dried at 50-60° C. under vacuum conditions for 8-10 h to obtain a modified polyurethane;
[0012] (2) Pretreated boron nitride, 4-propyleneoxy-2-hydroxybenzophenone, allyl phosphoric acid, and toluene are mixed uniformly in a mass ratio of 1:(0.5-0.6):(0.6-0.8):(20-22) to prepare a mixed solution, and azobisisobutyronitrile and toluene are mixed uniformly in a mass ratio of 1:(6-8) to prepare an azobisisobutyronitrile solution. In a nitrogen atmosphere, at 70-80° C. and 200-300 r / min stirring conditions, 0.4-0.6 times the mass of the mixed solution of azobisisobutyronitrile solution is uniformly added dropwise to the mixed solution within 20 minutes, and the stirring reaction is continued for 5-6 minutes. h, cooled to room temperature, filtered and washed with methanol and deionized water for 3 to 5 times, dried at 50 to 60°C for 8 to 10 hours under vacuum conditions to obtain pre-modified boron nitride; pre-modified boron nitride, N-(2-aminopropyl)maleimide, dicyclohexylcarbodiimide and toluene were mixed uniformly in a mass ratio of 1:(2 to 3):(0.03 to 0.05):(20 to 22), stirred at 75 to 85°C and 300 to 500 r / min for 2 to 3 hours, filtered, washed with anhydrous ethanol and deionized water for 3 to 5 times, dried at 50 to 60°C for 7 to 9 hours under vacuum conditions to obtain modified boron nitride;
[0013] (3) Modified polyurethane, modified boron nitride, and N,N-dimethylformamide are uniformly mixed in a mass ratio of 1:(0.03-0.04):(2.5-3.5) to prepare polyurethane paint; the copper wire is soaked in the polyurethane paint and then taken out, dried at 70-80° C. for 3-4 hours under vacuum conditions, and then soaked again, and the soaking-drying is repeated 2-4 times to obtain enameled wire for new energy photovoltaic power.
[0014] As an optimization, the preparation method of the polyurethane in step (1) is: 1-chloromethyl-2,4-diisocyanobenzene, hydroxyl-terminated polymethyltrifluoropropylsiloxane, and dimethylglyoxime are added in a mass ratio of 1:(0.3-0.4):(0.3-0.4) to N,N-dimethylformamide (20-24 times the mass of 1-chloromethyl-2,4-diisocyanobenzene), and the mixture is stirred and reacted at 60-70°C and 300-500 r / min under a nitrogen atmosphere. The reaction system is added with 1,6-hexanediol in an amount of 0.06 to 0.08 times the molar amount of 1-chloromethyl-2,4-diisocyanobenzene every half an hour, and the isocyanate group concentration of the reaction system is detected by dibutylamine-hydrochloric acid titration method. When the isocyanate group concentration is less than 3 to 4%, the addition of 1,6-hexanediol is stopped, and the remaining isocyanate groups are quenched with anhydrous ethanol. The reaction mixture is cooled to room temperature and dried at 50 to 60° C. for 6 to 7 hours under vacuum conditions to obtain a polyurethane.
[0015] As an optimization, the molecular weight of the hydroxyl-terminated polymethyltrifluoropropylsiloxane is 6000-8000.
[0016] As an optimization, the preparation method of the pretreated boron nitride in step (2) is: boron nitride and anhydrous ethanol are mixed uniformly in a mass ratio of 1: (50-60), silane hydrolyzate is added in an amount of 8-10 times the mass of boron nitride, the reaction is carried out at 50-60° C. and 300-500 r / min with stirring for 2-3 hours, filtered, washed with anhydrous ethanol for 3-5 times, and dried at 50-60° C. under vacuum conditions for 8-10 hours to obtain pretreated boron nitride.
[0017] As an optimization, the particle size of the boron nitride is 2 to 3 μm.
[0018] As an optimization, the preparation method of the silane hydrolyzate is: allyltriethoxysilane and anhydrous ethanol are mixed evenly in a mass ratio of 1:(20-30), the pH is adjusted to 4-6 with a 1 mol / L oxalic acid aqueous solution, and the mixture is stirred at 10-30° C. and 300-500 r / min for 50-60 min to prepare a silane hydrolyzate.
[0019] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0020] When preparing the enameled wire for new energy photovoltaic power, the present invention comprises the following steps: 1-chloromethyl-2,4-diisocyanobenzene, hydroxyl-terminated polymethyltrifluoropropylsiloxane and dimethylglyoxime are polymerized to obtain polyurethane; polyurethane and 1-(9-anthryl)methylamine are reacted to obtain modified polyurethane; boron nitride is treated with allyltriethoxysilane to obtain pretreated boron nitride; 4-propyleneoxy-2-hydroxybenzophenone and allyl phosphoric acid are polymerized and grown on the pretreated boron nitride to obtain premodified boron nitride; premodified boron nitride and N-(2-aminopropyl)maleimide are reacted to obtain modified boron nitride; modified polyurethane and modified boron nitride are prepared into polyurethane paint; copper wire is impregnated with the polyurethane paint and dried to obtain the enameled wire for new energy photovoltaic power.
[0021] First, 1-chloromethyl-2,4-diisocyanobenzene, hydroxyl-terminated polymethyltrifluoropropylsiloxane, and dimethylglyoxime are polymerized to obtain polyurethane; Si-O bonds and oxime urethane bonds are introduced into the main chain of polyurethane, and chloromethyl and trifluoropropyl groups are introduced into the side chain; the bond energy of Si-O bonds is greater than that of CC bonds, so compared with CC bonds, Si-O bonds need to absorb more heat and their own vibration energy to dissipate the energy of thermal decomposition of polymer materials. The layered SiO formed by the degradation of siloxane during combustion 2 Migrate to the surface of the carbon layer, making the carbon layer denser, inhibiting the oxidation of the carbon layer, enhancing the stability of the carbon layer at high temperatures, and giving the enameled wire for new energy photovoltaic power excellent flame retardant and thermal stability; the outer layer of the enameled wire may be damaged during use, and the oxime urethane bond can coordinate with the copper ions escaped from the copper wire to form a coordination bond to achieve self-repairing performance; the fluorine atom of the trifluoropropyl group has low reactivity and hydrophobicity, which can improve the hydrophobicity of the enameled wire for new energy photovoltaic power, thereby improving the corrosion resistance;
[0022] Secondly, the chloromethyl group introduced on the polyurethane side chain reacts with the amino group on 1-(9-anthryl)methylamine to obtain a modified polyurethane, and an anthracene group is introduced on the modified polyurethane side chain; the anthracene group can undergo a Diels-Alder addition reaction with the maleimide group on the modified boron nitride to form a thermally reversible cross-linked network, giving the enameled wire for new energy photovoltaic power excellent self-healing properties and mechanical properties;
[0023] Finally, the boron nitride is treated with allyltriethoxysilane to obtain pretreated boron nitride, and a carbon-carbon double bond is introduced into the pretreated boron nitride; 4-propyleneoxy-2-hydroxybenzophenone and allyl phosphoric acid are polymerized and grown on the pretreated boron nitride to obtain pre-modified boron nitride, and a 2-hydroxybenzophenone structure, a phosphorus element, and a phosphoric acid group are introduced into the pre-modified boron nitride; 2-hydroxybenzophenone is the main structure of benzophenone-type ultraviolet absorbers, which can absorb ultraviolet rays and give the enameled wire for new energy photovoltaic power excellent anti-aging properties; the phosphorus element can capture free radicals and promote the formation of a carbon layer to isolate heat and oxygen, further improving the flame retardant properties of the enameled wire for new energy photovoltaic power; the phosphoric acid group on the pre-modified boron nitride is bonded to the phosphoric acid group on N-(2-aminopropyl)maleimide. Modified boron nitride is prepared by amino reaction, and maleimide group is introduced into the modified boron nitride; the maleimide group can undergo Diels-Alder addition reaction with the anthracene group introduced on the side chain of modified polyurethane to form a thermally reversible cross-linking network, which gives the enameled wire for new energy photovoltaic power excellent self-healing performance and mechanical properties; boron nitride is an inorganic non-metallic material with excellent thermal conductivity and insulation. Boron nitride is modified to improve the compatibility of boron nitride with matrix resin, so that boron nitride is evenly dispersed in the matrix resin, and the performance of boron carbide is fully utilized to improve the thermal conductivity and insulation of the enameled wire for new energy photovoltaic power. The improvement of thermal conductivity can inhibit the thermal oxidation aging of the outer paint film of the enameled wire, and further improve the anti-aging performance of the enameled wire for new energy photovoltaic power. DETAILED DESCRIPTION
[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0025] Example 1
[0026] A preparation process of an enameled wire for new energy photovoltaic power, the preparation process of the enameled wire for new energy photovoltaic power comprising the following preparation steps:
[0027] (1) 1-chloromethyl-2,4-diisocyanobenzene, hydroxyl-terminated polymethyltrifluoropropylsiloxane, and dimethylglyoxime were added to N,N-dimethylformamide (20 times the mass of 1-chloromethyl-2,4-diisocyanobenzene) in a mass ratio of 1:0.3:0.3, and the mixture was stirred at 60°C and 300 r / min under a nitrogen atmosphere to react. 1,6-hexanediol (0.06 times the molar amount of 1-chloromethyl-2,4-diisocyanobenzene) was added to the reaction system every half an hour, and the reaction was detected by dibutylamine-hydrochloric acid titration method. The isocyanate group concentration of the system was determined. When the isocyanate group concentration was less than 3%, the addition of 1,6-hexanediol was stopped, the remaining isocyanate groups were quenched with anhydrous ethanol, the mixture was cooled to room temperature, and dried at 50°C for 7 hours under vacuum conditions to obtain polyurethane. Polyurethane, 1-(9-anthryl)methylamine, triethylamine, and N,N-dimethylformamide were uniformly mixed in a mass ratio of 1:0.4:0.02:10, the mixture was stirred at 40°C and 300 r / min for 3 hours, and dried at 50°C for 10 hours under vacuum conditions to obtain modified polyurethane.
[0028] (2) Allyl triethoxysilane and anhydrous ethanol were mixed at a mass ratio of 1:20, the pH was adjusted to 4 with a 1 mol / L oxalic acid aqueous solution, and the mixture was stirred at 10°C and 300 r / min for 60 min to prepare a silane hydrolyzate; boron nitride and anhydrous ethanol were mixed at a mass ratio of 1:50, 8 times the mass of boron nitride was added to the silane hydrolyzate, and the mixture was stirred at 50°C and 300 r / min for 3 h, filtered, washed with anhydrous ethanol for 3 times, and dried at 50°C under vacuum for 10 h to prepare pretreated boron nitride; pretreated boron nitride, 4-propyleneoxy-2-hydroxybenzophenone, allyl phosphoric acid, and toluene were mixed at a mass ratio of 1:0.5:0.6:20 to prepare a mixed solution, and azobisisobutyronitrile and toluene were added at a mass ratio of 1:1. :6 mixed evenly to prepare an azobisisobutyronitrile solution, in a nitrogen atmosphere, at 70°C, 200r / min stirring conditions, 0.4 times the mass of the mixed solution of azobisisobutyronitrile solution was uniformly added dropwise to the mixed solution within 20min, and the stirring reaction was continued for 6h, cooled to room temperature, filtered and washed with methanol and deionized water 3 times each, and dried at 50°C for 10h under vacuum conditions to obtain pre-modified boron nitride; pre-modified boron nitride, N-(2-aminopropyl)maleimide, dicyclohexylcarbodiimide, and toluene were mixed evenly in a mass ratio of 1:2:0.03:20, stirred at 75°C, 300r / min for 3h, filtered, washed with anhydrous ethanol and deionized water 3 times each, and dried at 50°C for 9h under vacuum conditions to obtain modified boron nitride;
[0029] (3) Modified polyurethane, modified boron nitride, and N,N-dimethylformamide are uniformly mixed in a mass ratio of 1:0.03:2.5 to prepare polyurethane paint; a copper wire is soaked in the polyurethane paint and then taken out, dried at 70°C for 4 hours under vacuum conditions, and then soaked again, and the soaking-drying is repeated twice to obtain an enameled wire for new energy photovoltaic power.
[0030] Example 2
[0031] A preparation process of an enameled wire for new energy photovoltaic power, the preparation process of the enameled wire for new energy photovoltaic power comprising the following preparation steps:
[0032] (1) 1-chloromethyl-2,4-diisocyanobenzene, hydroxyl-terminated polymethyltrifluoropropylsiloxane, and dimethylglyoxime were added to N,N-dimethylformamide (22 times the mass of 1-chloromethyl-2,4-diisocyanobenzene) in a mass ratio of 1:0.35:0.35, and the mixture was stirred at 65°C and 400 r / min under a nitrogen atmosphere to react. 1,6-hexanediol (0.07 times the molar amount of 1-chloromethyl-2,4-diisocyanobenzene) was added to the reaction system every half an hour, and the reaction system was detected by dibutylamine-hydrochloric acid titration method. The isocyanate group concentration is adjusted, when the isocyanate group concentration is less than 3.5%, the addition of 1,6-hexanediol is stopped, the remaining isocyanate groups are quenched with anhydrous ethanol, cooled to room temperature, and dried at 55°C for 6.5 hours under vacuum conditions to obtain polyurethane; polyurethane, 1-(9-anthryl)methylamine, triethylamine, and N,N-dimethylformamide are uniformly mixed in a mass ratio of 1:0.5:0.03:11, stirred at 45°C and 400r / min for reaction for 2.5 hours, and dried at 55°C for 9 hours under vacuum conditions to obtain modified polyurethane;
[0033] (2) Allyl triethoxysilane and anhydrous ethanol were mixed at a mass ratio of 1:25, the pH was adjusted to 5 with a 1 mol / L oxalic acid aqueous solution, and the mixture was stirred at 20°C and 400 r / min for 55 min to prepare a silane hydrolyzate; boron nitride and anhydrous ethanol were mixed at a mass ratio of 1:55, 9 times the mass of boron nitride was added to the silane hydrolyzate, and the mixture was stirred at 55°C and 400 r / min for 2.5 h, filtered, washed with anhydrous ethanol for 4 times, and dried at 55°C under vacuum for 9 h to prepare pretreated boron nitride; pretreated boron nitride, 4-propyleneoxy-2-hydroxybenzophenone, allyl phosphoric acid, and toluene were mixed at a mass ratio of 1:0.55:0.7:21 to prepare a mixed solution, and azobisisobutyronitrile and toluene were added at a mass ratio of 1: 7. Mix well to prepare azobisisobutyronitrile solution. In a nitrogen atmosphere, under stirring conditions of 75°C and 250r / min, add 0.5 times the mass of azobisisobutyronitrile solution to the mixed solution at a uniform rate within 20min, continue stirring and reacting for 5.5h, cool to room temperature, filter and wash with methanol and deionized water 4 times each, and dry at 55°C for 9h under vacuum conditions to obtain pre-modified boron nitride; mix pre-modified boron nitride, N-(2-aminopropyl)maleimide, dicyclohexylcarbodiimide, and toluene in a mass ratio of 1:2.5:0.04:21, stir and react at 80°C and 400r / min for 2.5h, filter, wash with anhydrous ethanol and deionized water 4 times each, and dry at 55°C for 8h under vacuum conditions to obtain modified boron nitride;
[0034] (3) Modified polyurethane, modified boron nitride, and N,N-dimethylformamide are uniformly mixed in a mass ratio of 1:0.035:3 to prepare polyurethane paint; a copper wire is soaked in the polyurethane paint and then taken out, dried at 75°C for 3.5 hours under vacuum conditions, and then soaked again, and the soaking-drying is repeated three times to obtain an enameled wire for new energy photovoltaic power.
[0035] Example 3
[0036] A preparation process of an enameled wire for new energy photovoltaic power, the preparation process of the enameled wire for new energy photovoltaic power comprising the following preparation steps:
[0037] (1) 1-chloromethyl-2,4-diisocyanobenzene, hydroxyl-terminated polymethyltrifluoropropylsiloxane, and dimethylglyoxime were added to N,N-dimethylformamide (24 times the mass of 1-chloromethyl-2,4-diisocyanobenzene) in a mass ratio of 1:0.4:0.4, and the mixture was stirred at 70°C and 500 r / min under a nitrogen atmosphere to react. 1,6-hexanediol (0.08 times the molar amount of 1-chloromethyl-2,4-diisocyanobenzene) was added to the reaction system every half an hour, and the reaction was detected by dibutylamine-hydrochloric acid titration method. The isocyanate group concentration of the system was adjusted. When the isocyanate group concentration was less than 4%, the addition of 1,6-hexanediol was stopped, the remaining isocyanate groups were quenched with anhydrous ethanol, and the mixture was cooled to room temperature. The mixture was dried at 60°C for 6 hours under vacuum conditions to obtain polyurethane. Polyurethane, 1-(9-anthryl)methylamine, triethylamine, and N,N-dimethylformamide were uniformly mixed in a mass ratio of 1:0.6:0.04:12, and the mixture was stirred at 50°C and 500 r / min for 2 hours. The mixture was dried at 60°C for 8 hours under vacuum conditions to obtain modified polyurethane.
[0038] (2) Allyl triethoxysilane and anhydrous ethanol were mixed at a mass ratio of 1:30, the pH was adjusted to 6 with a 1 mol / L oxalic acid aqueous solution, and the mixture was stirred at 30°C and 500 r / min for 50 min to prepare a silane hydrolyzate; boron nitride and anhydrous ethanol were mixed at a mass ratio of 1:60, 10 times the mass of boron nitride was added to the silane hydrolyzate, and the mixture was stirred at 60°C and 500 r / min for 2 h, filtered, washed with anhydrous ethanol for 5 times, and dried at 60°C under vacuum for 8 h to prepare pretreated boron nitride; pretreated boron nitride, 4-propyleneoxy-2-hydroxybenzophenone, allyl phosphoric acid, and toluene were mixed at a mass ratio of 1:0.6:0.8:22 to prepare a mixed solution, and azobisisobutyronitrile and toluene were added at a mass ratio of 1:8 was mixed evenly to prepare an azobisisobutyronitrile solution, and in a nitrogen atmosphere, under the stirring conditions of 80°C and 300r / min, 0.6 times the mass of the mixed solution of azobisisobutyronitrile solution was uniformly added dropwise to the mixed solution within 20min, and the stirring reaction was continued for 5h, cooled to room temperature, filtered and washed with methanol and deionized water 5 times each, and dried at 60°C for 8h under vacuum conditions to obtain pre-modified boron nitride; pre-modified boron nitride, N-(2-aminopropyl)maleimide, dicyclohexylcarbodiimide, and toluene were mixed evenly in a mass ratio of 1:3:0.05:22, stirred and reacted at 85°C and 500r / min for 2h, filtered, washed with anhydrous ethanol and deionized water 5 times each, and dried at 60°C for 7h under vacuum conditions to obtain modified boron nitride;
[0039] (3) Modified polyurethane, modified boron nitride, and N,N-dimethylformamide are uniformly mixed in a mass ratio of 1:0.04:3.5 to prepare polyurethane paint; a copper wire is soaked in the polyurethane paint and then taken out, dried at 80°C for 3 hours under vacuum conditions, and then soaked again, and the soaking-drying is repeated 4 times to obtain an enameled wire for new energy photovoltaic power.
[0040] Comparative Example 1
[0041] The difference between the preparation process of the new energy photovoltaic power enameled wire of Comparative Example 1 and Example 2 lies in the difference in step (1). Step (1) is modified as follows: 1-chloromethyl-2,4-diisocyanatobenzene, hydroxyl-terminated polymethyltrifluoropropylsiloxane, and 1,6-hexanediol are added in a mass ratio of 1:0.35:0.35 to N,N-dimethylformamide (22 times the mass of 1-chloromethyl-2,4-diisocyanatobenzene), and the reaction is stirred at 65°C and 400r / min under a nitrogen atmosphere. 1,6-hexanediol (0.07 times the molar amount of 1-chloromethyl-2,4-diisocyanatobenzene) is added to the reaction system every half an hour. 6-hexanediol, and the isocyanate group concentration of the reaction system is detected by dibutylamine-hydrochloric acid titration method. When the isocyanate group concentration is less than 3.5%, stop adding 1,6-hexanediol, quench the remaining isocyanate groups with anhydrous ethanol, cool to room temperature, and dry at 55°C for 6.5h under vacuum conditions to obtain polyurethane; polyurethane, 1-(9-anthryl)methylamine, triethylamine, and N,N-dimethylformamide are mixed uniformly in a mass ratio of 1:0.5:0.03:11, stirred at 45°C, 400r / min for 2.5h, and dried at 55°C for 9h under vacuum conditions to obtain modified polyurethane. The remaining steps are the same as in Example 2.
[0042] Comparative Example 2
[0043] The difference between the preparation process of the new energy photovoltaic power enameled wire of Comparative Example 2 and Example 2 is that step (1) is different, and step (1) is modified as follows: 1-chloromethyl-2,4-diisocyanatobenzene, 1,6-hexanediol, and dimethylglyoxime are added to N,N-dimethylformamide with a mass ratio of 1:0.3:0.3, and the reaction is stirred at 60°C and 300r / min under a nitrogen atmosphere. 0.06 times the molar amount of 1-chloromethyl-2,4-diisocyanatobenzene is added to the reaction system every half an hour. Alcohol, and the isocyanate group concentration of the reaction system is detected by dibutylamine-hydrochloric acid titration method. When the isocyanate group concentration is less than 3%, stop adding 1,6-hexanediol, quench the remaining isocyanate groups with anhydrous ethanol, cool to room temperature, and dry at 50°C for 7 hours under vacuum conditions to obtain polyurethane; polyurethane, 1-(9-anthryl)methylamine, triethylamine, and N,N-dimethylformamide are mixed uniformly in a mass ratio of 1:0.4:0.02:10, stirred at 40°C, 300r / min for 3 hours, and dried at 50°C for 10 hours under vacuum conditions to obtain modified polyurethane. The remaining steps are the same as in Example 2.
[0044] Comparative Example 3
[0045] The preparation process of the new energy photovoltaic power enameled wire of Comparative Example 3 is different from that of Example 2 only in step (1). Step (1) is modified as follows: 1-chloromethyl-2,4-diisocyanatobenzene, hydroxyl-terminated polymethyltrifluoropropylsiloxane, and dimethylglyoxime are added to N,N-dimethylformamide (20 times the mass of 1-chloromethyl-2,4-diisocyanatobenzene) in a mass ratio of 1:0.3:0.3, and heated at 60°C, 300°C under a nitrogen atmosphere. r / min stirring reaction, adding 1,6-hexanediol of 0.06 times the molar amount of 1-chloromethyl-2,4-diisocyanobenzene to the reaction system every half an hour, and detecting the isocyanate group concentration of the reaction system by dibutylamine-hydrochloric acid titration method, when the isocyanate group concentration is less than 3%, stop adding 1,6-hexanediol, quench the remaining isocyanate groups with anhydrous ethanol, cool to room temperature, and dry at 50°C for 7 hours under vacuum conditions to obtain modified polyurethane. The remaining steps are the same as in Example 2.
[0046] Comparative Example 4
[0047] The preparation process of the new energy photovoltaic power enameled wire of Comparative Example 4 is different from that of Example 2 only in step (2). Step (2) is modified as follows: allyl triethoxysilane and anhydrous ethanol are mixed in a mass ratio of 1:25, the pH is adjusted to 5 with a 1 mol / L oxalic acid aqueous solution, and stirred at 20°C and 400 r / min for 55 min to prepare a silane hydrolyzate; boron nitride and anhydrous ethanol are mixed in a mass ratio of 1:55, 9 times the mass of boron nitride is added to the silane hydrolyzate, stirred at 55°C and 400 r / min for 2.5 h, filtered, washed with anhydrous ethanol 4 times, and dried at 55°C under vacuum for 9 h to prepare pretreated boron nitride; pretreated boron nitride, propylene, allyl phosphoric acid, and toluene are mixed in a mass ratio of 1:0.55:0.7:21 to prepare a mixed solution. Azobisisobutyronitrile and toluene were mixed uniformly in a mass ratio of 1:7 to prepare an azobisisobutyronitrile solution. In a nitrogen atmosphere, under stirring conditions of 75°C and 250r / min, 0.5 times the mass of the mixed solution of azobisisobutyronitrile solution was uniformly added to the mixed solution within 20min, and the mixture was stirred for 5.5h. The mixture was cooled to room temperature, filtered and washed with methanol and deionized water 4 times each, and dried at 55°C for 9h under vacuum conditions to obtain pre-modified boron nitride; pre-modified boron nitride, N-(2-aminopropyl)maleimide, dicyclohexylcarbodiimide, and toluene were mixed uniformly in a mass ratio of 1:2.5:0.04:21, stirred and reacted at 80°C and 400r / min for 2.5h, filtered, washed with anhydrous ethanol and deionized water 4 times each, and dried at 55°C for 8h under vacuum conditions to obtain modified boron nitride. The remaining steps are the same as in Example 2.
[0048] Comparative Example 5
[0049] The preparation process of the new energy photovoltaic power enameled wire of Comparative Example 5 is different from that of Example 2 only in step (2). Step (2) is modified as follows: allyl triethoxysilane and anhydrous ethanol are mixed in a mass ratio of 1:25, the pH is adjusted to 5 with a 1 mol / L oxalic acid aqueous solution, and stirred at 20°C and 400 r / min for 55 min to prepare a silane hydrolyzate; boron nitride and anhydrous ethanol are mixed in a mass ratio of 1:55, silane hydrolyzate with 9 times the mass of boron nitride is added, and the reaction is stirred at 55°C and 400 r / min for 2.5 h, filtered, washed 4 times with anhydrous ethanol, and dried at 55°C under vacuum for 9 h to obtain Pretreatment of boron nitride: pretreatment of boron nitride, 4-propyleneoxy-2-hydroxybenzophenone, propylene, and toluene are mixed in a mass ratio of 1:0.55:0.7:21 to prepare a mixed solution, azobisisobutyronitrile and toluene are mixed in a mass ratio of 1:7 to prepare an azobisisobutyronitrile solution, and in a nitrogen atmosphere, at 75°C, 250r / min stirring conditions, 0.5 times the mass of the mixed solution of azobisisobutyronitrile solution is uniformly added to the mixed solution within 20min, stirring and reacting for 5.5h, cooling to room temperature, and washing with methanol and deionized water by suction for 4 times, and drying at 55°C for 9h under vacuum conditions to obtain modified boron nitride. The remaining steps are the same as those in Example 2.
[0050] Test Example 1
[0051] Flame retardant performance test
[0052] Test method: Pour the polyurethane paint prepared in the embodiment and the comparative example into a mold, dry it at 70°C for 10 hours under vacuum conditions, prepare it into a standard specimen according to GB / T2406.2, and test the limiting oxygen index of the standard specimen. The results are shown in Table 1.
[0053] Table 1
[0054] Limiting oxygen index (%) Limiting oxygen index (%) Example 1 32.67 Comparative Example 1 32.15 Example 2 33.14 Comparative Example 2 26.41 Example 3 33.04 Comparative Example 3 32.09 Comparative Example 4 32.32 Comparative Example 5 25.84
[0055] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 1, it can be found that the new energy photovoltaic power enameled wire prepared by the present invention has good flame retardant properties.
[0056] By comparison, the limiting oxygen index of Examples 1 to 3 is greater than that of Comparative Example 2, indicating that polyurethane is prepared by polymerization of 1-chloromethyl-2,4-diisocyanobenzene, hydroxyl-terminated polymethyltrifluoropropylsiloxane, and dimethylglyoxime; Si-O bonds are introduced into the main chain of polyurethane, and the bond energy of Si-O bonds is greater than that of CC bonds. Therefore, compared with CC bonds, Si-O bonds need to absorb more heat and their own vibration energy to dissipate the energy of thermal decomposition of polymer materials. The layered SiO formed by degradation during combustion of siloxane is 2Migrate to the surface of the carbon layer, make the carbon layer denser, inhibit the oxidation of the carbon layer, enhance the stability of the carbon layer at high temperature, and endow the enameled wire for new energy photovoltaic power with excellent flame retardant properties.
[0057] By comparison, the limiting oxygen index of Examples 1 to 3 is greater than that of Comparative Example 5, indicating that the boron nitride is treated with allyltriethoxysilane to obtain pretreated boron nitride, and a carbon-carbon double bond is introduced into the pretreated boron nitride; 4-propyleneoxy-2-hydroxybenzophenone and allyl phosphoric acid are polymerized and grown on the pretreated boron nitride to obtain pre-modified boron nitride, and phosphorus is introduced into the pre-modified boron nitride; the phosphorus element can capture free radicals and promote the formation of a carbon layer to isolate heat and oxygen, thereby further improving the flame retardant properties of the enameled wire for new energy photovoltaic power.
[0058] Test Example 2
[0059] Anti-aging performance test
[0060] Test method: Pour the polyurethane paint prepared in the embodiment and the comparative example into a mold, dry it at 70°C for 10 hours under vacuum conditions, prepare it into a standard sample according to GB / T13022, and test its tensile strength on an electronic universal testing machine. Put the unstretched standard sample into a light-oxidation aging test box, irradiate it at a 380nm ultraviolet wavelength for 7 days, and test the tensile strength of the standard sample on an electronic universal testing machine according to GB / T13022. Calculate the change rate of the tensile strength of the embodiment and the comparative example before and after the light-oxidation aging treatment. The results are shown in Table 2.
[0061] Table 2
[0062]
[0063]
[0064] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 2, it can be found that the new energy photovoltaic power enameled wire prepared by the present invention has good anti-aging performance.
[0065] By comparison, the change rate of tensile strength of Examples 1 to 3 is less than that of Comparative Example 4, indicating that the boron nitride is treated with allyltriethoxysilane to obtain pretreated boron nitride, and a carbon-carbon double bond is introduced into the pretreated boron nitride; 4-propyleneoxy-2-hydroxybenzophenone and allyl phosphoric acid are polymerized and grown on the pretreated boron nitride to obtain pre-modified boron nitride, and a 2-hydroxybenzophenone structure is introduced into the pre-modified boron nitride; 2-hydroxybenzophenone is the main structure of benzophenone-type ultraviolet absorbers, which can absorb ultraviolet rays and give the enameled wire for new energy photovoltaic power excellent anti-aging properties.
[0066] Test Example 3
[0067] Corrosion resistance test
[0068] Test method: Pour the polyurethane paint prepared in the embodiment and the comparative example into a mold, dry it at 70°C for 10 hours under vacuum conditions, take it out, and test the water drop contact angle using the sessile drop method on an OCA20 contact angle meter, with a water drop volume of 5 μL. The results are shown in Table 3.
[0069] Table 3
[0070]
[0071]
[0072] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 3, it can be found that the new energy photovoltaic power enameled wire prepared by the present invention has good corrosion resistance.
[0073] By comparison, the contact angles of Examples 1 to 3 are greater than the contact angle of Comparative Example 2, indicating that polyurethane is prepared by polymerization of 1-chloromethyl-2,4-diisocyanobenzene, hydroxyl-terminated polymethyltrifluoropropylsiloxane, and dimethylglyoxime; trifluoropropyl groups are introduced into the side chains of polyurethane; the fluorine atom of the trifluoropropyl group has low reactivity and hydrophobicity, which can improve the hydrophobicity of the enameled wire for new energy photovoltaic power, thereby improving the corrosion resistance.
[0074] Test Example 4
[0075] Self-healing performance test
[0076] Test method for thermal response self-repairing performance: According to GB / T1040.1, the polyurethane paint prepared in the embodiment and the comparative example is prepared into a standard specimen, and its original tensile strength is tested with a tensile machine. Then, a slit with a depth of 2mm and a length of 20mm is cut from the middle of the unstretched original specimen, and the specimen is placed in a mold, kept at 5Pa, 120℃ for 30min, and then kept at 5Pa, 60℃ for 24h to obtain the repaired specimen. The tensile strength is tested with a tensile machine. The thermal response self-repairing rate of the embodiment and the comparative example before and after repair is calculated, and the thermal response self-repairing rate = (tensile strength of the specimen after repair / original tensile strength of the specimen) × 100%. The results are shown in Table 4.
[0077] Test method for metal response self-repairing performance: According to GB / T1040.1, the polyurethane paint prepared in the embodiment and the comparative example is prepared into standard specimens, and its original tensile strength is tested with a tensile machine. Then, a 2mm deep and 20mm long crack is cut in the middle of the unstretched original specimen, immersed in a copper ion solution with a mass fraction of 6%, allowed to stand for 24 hours, taken out, and dried at 5Pa and 60°C for 6 hours to obtain the repaired specimen. The tensile strength is tested with a tensile machine. The metal response self-repairing rate of the embodiment and the comparative example before and after repair is calculated, and the metal response self-repairing rate = (tensile strength of the specimen after repair / original tensile strength of the specimen)
[0078] × 100%. The results are shown in Table 4.
[0079] Table 4
[0080]
[0081]
[0082] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 4, it can be found that the new energy photovoltaic power enameled wire prepared by the present invention has good self-repairing performance.
[0083] By comparison, the thermal response self-repairing rates of Examples 1 to 3 are greater than that of Comparative Example 3, indicating that polyurethane is prepared by polymerization of 1-chloromethyl-2,4-diisocyanobenzene, hydroxyl-terminated polymethyltrifluoropropylsiloxane, and dimethylglyoxime; chloromethyl is introduced into the side chain of the polyurethane; the chloromethyl introduced into the side chain of the polyurethane is reacted with the amino group on 1-(9-anthryl)methylamine to prepare a modified polyurethane, and anthracene groups are introduced into the side chain of the modified polyurethane; the anthracene groups can undergo a Diels-Alder addition reaction with the maleimide groups on the modified boron nitride to form a thermally reversible cross-linked network, thereby giving the new energy photovoltaic power enameled wire excellent self-repairing properties.
[0084] By comparison, the thermal response self-repair rate of Examples 1 to 3 is greater than that of Comparative Example 5, indicating that the boron nitride is treated with allyltriethoxysilane to obtain pretreated boron nitride, and a carbon-carbon double bond is introduced into the pretreated boron nitride; 4-propyleneoxy-2-hydroxybenzophenone and allyl phosphoric acid are polymerized and grown on the pretreated boron nitride to obtain pre-modified boron nitride, and a phosphate group is introduced into the pre-modified boron nitride; the phosphate group on the pre-modified boron nitride is reacted with the amino group on N-(2-aminopropyl)maleimide to obtain modified boron nitride, and a maleimide group is introduced into the modified boron nitride; the maleimide group can undergo a Diels-Alder addition reaction with the anthracene group introduced on the side chain of the modified polyurethane to form a thermally reversible cross-linked network, thereby giving the enameled wire for new energy photovoltaic power excellent self-repairing properties.
[0085] By comparison, the metal response self-repair rate of Examples 1 to 3 is greater than that of Comparative Example 1, indicating that polyurethane is prepared by polymerization of 1-chloromethyl-2,4-diisocyanobenzene, hydroxyl-terminated polymethyltrifluoropropylsiloxane, and dimethylglyoxime; an oxime urethane bond is introduced into the main chain of the polyurethane, and the outer layer of the enameled wire may be damaged during use. The oxime urethane bond can coordinate with the copper ions escaped from the copper wire to form a coordination bond, thereby achieving self-repair performance.
[0086] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A preparation process for enameled wire for new energy photovoltaic power, characterized in that: The preparation process of the enameled wire for new energy photovoltaic power generation comprises the following steps: reacting polyurethane and 1-(9-anthryl)methylamine to obtain modified polyurethane; reacting pre-modified boron nitride and N-(2-aminopropyl)maleimide to obtain modified boron nitride; preparing polyurethane paint by mixing the modified polyurethane and the modified boron nitride; and impregnating the copper wire with the polyurethane paint and drying the copper wire to obtain the enameled wire for new energy photovoltaic power generation; The polyurethane is prepared by polymerization reaction of 1-chloromethyl-2,4-diisocyanobenzene, hydroxyl-terminated polymethyltrifluoropropylsiloxane and dimethylglyoxime; The pre-modified boron nitride is prepared by polymerizing 4-propyleneoxy-2-hydroxybenzophenone and allyl phosphoric acid on pre-treated boron nitride; The pretreated boron nitride is prepared by treating boron nitride with allyltriethoxysilane.
2. The preparation process of a new energy photovoltaic power enameled wire according to claim 1, characterized in that: The preparation process of the enameled wire for new energy photovoltaic power comprises the following preparation steps: (1) Polyurethane, 1-(9-anthryl)methylamine, triethylamine, and N,N-dimethylformamide are uniformly mixed in a mass ratio of 1:(0.4-0.6):(0.02-0.04):(10-12), stirred at 40-50° C. and 300-500 r / min for 2-3 h, and dried at 50-60° C. under vacuum conditions for 8-10 h to obtain a modified polyurethane; (2) Pretreated boron nitride, 4-propyleneoxy-2-hydroxybenzophenone, allyl phosphoric acid, and toluene are mixed uniformly in a mass ratio of 1:(0.5-0.6):(0.6-0.8):(20-22) to prepare a mixed solution, and azobisisobutyronitrile and toluene are mixed uniformly in a mass ratio of 1:(6-8) to prepare an azobisisobutyronitrile solution. In a nitrogen atmosphere, at 70-80° C. and 200-300 r / min stirring conditions, 0.4-0.6 times the mass of the mixed solution of azobisisobutyronitrile solution is uniformly added dropwise to the mixed solution within 20 minutes, and the stirring reaction is continued for 5-6 minutes. h, cooled to room temperature, filtered and washed with methanol and deionized water for 3 to 5 times, dried at 50 to 60°C for 8 to 10 hours under vacuum conditions to obtain pre-modified boron nitride; pre-modified boron nitride, N-(2-aminopropyl)maleimide, dicyclohexylcarbodiimide and toluene were mixed uniformly in a mass ratio of 1:(2 to 3):(0.03 to 0.05):(20 to 22), stirred at 75 to 85°C and 300 to 500 r / min for 2 to 3 hours, filtered, washed with anhydrous ethanol and deionized water for 3 to 5 times, dried at 50 to 60°C for 7 to 9 hours under vacuum conditions to obtain modified boron nitride; (3) Modified polyurethane, modified boron nitride, and N,N-dimethylformamide are uniformly mixed in a mass ratio of 1:(0.03-0.04):(2.5-3.5) to prepare polyurethane paint; the copper wire is soaked in the polyurethane paint and then taken out, dried at 70-80° C. for 3-4 hours under vacuum conditions, and then soaked again, and the soaking-drying is repeated 2-4 times to obtain enameled wire for new energy photovoltaic power.
3. The preparation process of a new energy photovoltaic power enameled wire according to claim 2, characterized in that: The preparation method of the polyurethane in step (1) is as follows: 1-chloromethyl-2,4-diisocyanobenzene, hydroxyl-terminated polymethyltrifluoropropylsiloxane, and dimethylglyoxime are added to N,N-dimethylformamide (20 to 24 times the mass of 1-chloromethyl-2,4-diisocyanobenzene) in a mass ratio of 1:(0.3 to 0.4):(0.3 to 0.4), and the mixture is stirred at 60 to 70° C. and 300 to 500 r / min under a nitrogen atmosphere for reaction. Add 1,6-hexanediol in an amount of 0.06 to 0.08 times the molar amount of 1-chloromethyl-2,4-diisocyanobenzene to the reaction system every half an hour, and detect the isocyanate group concentration of the reaction system by dibutylamine-hydrochloric acid titration method. When the isocyanate group concentration is less than 3 to 4%, stop adding 1,6-hexanediol, quench the remaining isocyanate groups with anhydrous ethanol, cool to room temperature, and dry at 50 to 60° C. for 6 to 7 hours under vacuum conditions to obtain polyurethane.
4. The preparation process of a new energy photovoltaic power enameled wire according to claim 3, characterized in that: The molecular weight of the hydroxyl-terminated polymethyltrifluoropropylsiloxane is 6,000-8,000.
5. The preparation process of a new energy photovoltaic power enameled wire according to claim 2, characterized in that: The preparation method of the pretreated boron nitride in step (2) is as follows: boron nitride and anhydrous ethanol are mixed uniformly in a mass ratio of 1: (50-60), silane hydrolyzate is added in an amount of 8-10 times the mass of the boron nitride, the reaction is carried out at 50-60° C. and 300-500 r / min with stirring for 2-3 hours, the reaction is filtered, the reaction is washed with anhydrous ethanol for 3-5 times, and the pretreated boron nitride is dried at 50-60° C. under vacuum conditions for 8-10 hours to obtain the pretreated boron nitride.
6. The preparation process of a new energy photovoltaic power enameled wire according to claim 5, characterized in that: The particle size of the boron nitride is 2-3 μm.
7. The preparation process of a new energy photovoltaic power enameled wire according to claim 5, characterized in that: The preparation method of the silane hydrolyzate is as follows: allyl triethoxysilane and anhydrous ethanol are uniformly mixed in a mass ratio of 1:(20-30), the pH value is adjusted to 4-6 with a 1 mol / L oxalic acid aqueous solution, and the silane hydrolyzate is prepared by stirring at 10-30° C. and 300-500 r / min for 50-60 min.
